OPTIMIZATION OF TOKENIZATION AND MEMORY MANAGEMENT FOR PROCESSING LARGE TEXTUAL CORPORA IN MULTILINGUAL APPLICATIONS - Dodić, Dejan; Regodić, Dušan; Milutinović, Nikola (Bulletin of Natural Sciences Research, 2025)
Optimization of tokenization and memory management in processing large datasets represents a key challenge in the contemporary development of language models. This paper focuses on enhancing the processing of large textual corpora in Serbian using the GPT-2 model, specifically adapted for transfer learning. Tokenization optimization was achieved by adding language-specific tokens for Serbian, while memory management was improved through advanced resource management methods during training. Key findings demonstrate significant memory consumption reduction and training process acceleration, enabling more efficient utilization of available computational resources. This research contributes to the development of language models tailored for the Serbian language and provides a foundation for further studies in the field of natural language processing (NLP). The implications of this work are multifaceted: it facilitates more efficient creation of NLP applications for Serbian-speaking regions, enhances the accuracy and performance of language models, and opens opportunities for applications across various domains, from automated translation to sentiment analysis. This study paves the way for future research focusing on additional optimization of language models, including adaptation for other languages with similar characteristics, as well as exploring new methods for even more efficient memory management during large-scale textual data processing.